Pelatihan Soft Skill Untuk Meningkatkan Kualitas Dan Mutu Layanan PAUD Di Desa Ngagel - Sumiyati Sumiyati (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2020)
This research is based on community service at the village of Ngagel, Dukuhseti District, Pati Regency. against the background of the education level of the Ngagel village community which is still low, and the quality of Early Childhood Education Institutions (PAUD) that are not in accordance with the principles of Early Childhood learning. Educators in early childhood education institutions in Ngagel village do not yet have an undergraduate education qualification, the majority are high school graduates. the teachers do not understand the ways to manage PAUD well, including not yet understanding how to make learning plans and prepare learning media that will be used in the learning process.Seeing this background, the community service program has a service program, especially in the field of education. This work program covers three main things namely; soft skills training, mentoring institutions and the formation of tutoring activities. All three of these programs is solution. Our soft skills training and institutional assistance is intended for teachers and institutions both PAUD and at the level of basic education, in order to improve the quality of learning at each level. while tutoring is intended for students from PAUD to high school. This program was quite successful with the full support of the local village government, namely the Ngagel village government along with the Ngagel village community leaders. Likewise, the high interest in learning from teachers and children in the village of Ngagel.